Image quality for visualization of cracks and fine endodontic structures using 10 CBCT devices with various scanning protocols and artefact conditions - Pinto, Jáder Camilo [UNESP] (2023)
The aim of this study was to evaluate CBCT exposure protocols and CBCT devices in terms of image quality for the detection of cracks and fine endodontic structures using 3 conditions of metallic artifacts. An anthropomorphic phantom containing teeth with cracks, isthmus, narrow canal, and apical delta was scanned using ten CBCT devices. A reference industrial CT image was used to detect and measure all structures. Three conditions were created: (1) metal-free, (2) ‘endo’ and (3) ‘implant’ with metallic objects placed next to the teeth of interest. For each condition, three protocols were selected: medium field of view (FOV) standard resolution, small FOV standard and high resolution. The results showed that only small FOV high-resolution metal-free images from two devices (A and H) were appropriate to visualize cracks. For fine structure identification, the best result was observed for small FOV high resolution. However, the visualization significantly worsened in the presence of metallic artefacts. The ability of CBCT images for visualizing cracks is restricted to certain CBCT devices. Once metallic artefacts are present, crack detection becomes unlikely. Overall, small FOV high-resolution protocols may allow detection of fine endodontic structures as long as there are no high-dense objects in the region of interest.